Hubungan Antara Kontrol Diri Dengan Kecanduan Game Online Pada Siswa SMA Negeri 1 Godong - Niken Larasati (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
The background of this study is the increasing interest of students in online games, resulting in negative impacts on students, namely students becoming addicted to online games, so that students have difficulty managing time due to lack of selfcontrol. The purpose of this study is to determine the relationship between selfcontrol and online game addiction in grade XI students at SMA Negeri 1 Godong. The research method used is quantitative. The data collection process was carried out by distributing questionnaires to 30 grade XI 1 students of SMA Negeri 1 Godong. The results of this study are based on hypothesis testing using Pearson correlation, obtained a correlation coefficient value of 0.569 with a significance of 0.000, so this value indicates that there is a statistically significant relationship between self-control and online game addiction.